Malgudi Adventures: Classic Tales for Children - R. K. Narayan (Puffin Books, 2004)
Unforgettable stories for children from the masterly pen of R.K. Narayan After the stupendous success of Malgudi Schooldays, R.K. Narayan's chronicle of the escapades of Swami and his friends comes Malgudi Adventures, which contains more delightful stories of children's adventures in the magical South Indian small town of Malgudi. There are the memorable stories of Babu, who, in trying to set up the lights for his sisters' Navaratri display, manages to plunge the entire household into darkness; of a snake charmer boy who grows up with a monkey named Rama as his companion; and of Raju, who decides to become a guide when a train station is built at Malgudi. Also included are the fascinating stories of Balu, who dumps his father's accounts ledger in the gutter; of a little boy who finds himself lost on the streets of Malgudi late one night; of Chandran, who falls head over heels in love on the banks of the Sarayu one evening; and of the hilarious sequence of events that unfolds when Raja the tiger decides to seek refuge in the local school.